Advanced topics in Java : core concepts in data structures - Kalicharan, Noel (Expert's voice in Java., 2014)
Java is one of the most widely used programming languages today. It was first released by Sun Microsystems in 1995. Over the years, its popularity has grown to the point where it plays an important role in most of our lives. From laptops to data centers, game consoles to scientific supercomputers, cell phones to the Internet, Java is everywhere! There are tons of applications and heaps of websites that will not work unless you have Java installed, and more are created every day. And, of course, Java is used to power what has become the world's most dominant mobile platform, Android. Advanced Topics In Java teaches the algorithms and concepts that any budding software developer should know. You'll delve into topics such as sorting, searching, merging, recursion, random numbers and simulation, among others. You will increase the range of problems you can solve when you learn how to create and manipulate versatile and popular data structures such as binary trees and hash tables. This book assumes you have a working knowledge of basic programming concepts such as variables, constants, assignment, selection (if.else) and looping (while, for). It also assumes you are comfortable with writing functions and working with arrays. If you study this book carefully and do the exercises conscientiously, you would become a better and more agile software developer, more prepared to code today's applications - no matter the language.